2010
DOI: 10.1086/656307
|View full text |Cite
|
Sign up to set email alerts
|

A Fish Out of Water: Gill and Skin Remodeling Promotes Osmo- and Ionoregulation in the Mangrove KillifishKryptolebias marmoratus

Abstract: The euryhaline, amphibious mangrove killifish Kryptolebias marmoratus is known to survive weeks out of water in moist environments. We tested the hypothesis that the skin is a site of osmo- and ionoregulation in K. marmoratus. We predicted that under terrestrial conditions, gill and skin remodeling would result in an enhanced role for skin and a diminished role for the gills in osmo- and ionoregulation. Fish were exposed to water-either freshwater (FW, 1‰) or hypersaline water (saltwater [SW], 45‰)-or air over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 67 publications
3
50
0
Order By: Relevance
“…We observed significant increases in the ILCMs of fish exposed to air or low ion water, as has been previously observed (Ong et al, 2007;LeBlanc et al, 2010). We also found that 7days of hypoxic acclimation significantly decreased the height of the ILCM in mangrove rivulus.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed significant increases in the ILCMs of fish exposed to air or low ion water, as has been previously observed (Ong et al, 2007;LeBlanc et al, 2010). We also found that 7days of hypoxic acclimation significantly decreased the height of the ILCM in mangrove rivulus.…”
Section: Discussionsupporting
confidence: 90%
“…While this is the first report of hypoxia-induced gill plasticity in K. marmoratus, this response was not surprising based on previous studies in hypoxia-acclimated cyprinid fishes, where an increase in gill surface area would likely facilitate oxygen uptake (Sollid et al, 2003;Matey et al, 2008;Mitrovic et al, 2009). Enlarged ILCMs during acclimation to low ion water is thought to reduce ion loss at the expense of reduced respiratory function according to the osmorespiratory compromise hypothesis (Gonzalez and McDonald, 1992;LeBlanc et al, 2010).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The kidney is one organ that became more important in ionoregulation (Smith 1959;Brauner et al 2004), but the kidney can only retain and regulate ions, not acquire them from the environment, which is a critical requirement for freshwater fish. There is also evidence that the skin became an important site of ion uptake, at least transitionally (Wilkie et al 2007;LeBlanc et al 2010), but in the longer term, it seems that this function must have been taken over by the gut once contact with water was lost during the evolutionary transition to life on land.…”
Section: Introductionmentioning
confidence: 99%
“…Yokota et al, 1997;LeBlanc et al, 2010;Itoki et al, 2012;Cooper et al, 2013). In K. marmoratus acclimated to air on a hypersaline surface, skin ionocyte cross-sectional area increased, although ionoregulation was not perfectly maintained, as whole-body Na + levels were 30% higher relative to those of control fish in water .…”
Section: Water Availability and Ion Balancementioning
confidence: 95%